Optimalisasi Pengelolaan Sampah Plastik dalam Upaya Menunjang Kebersihan dan Ekonomi Wisata Pantai Nirwana Kota Baubau - Rudi Abdullah; Dedy Felly Firdaus M.; Hamdan Hamdan; Zulkifli Azis; Wa Ode Arniati; Fira Amran; Windi Apriliya; Wa Ode Armi Ningsi; La Ode Rajab Hibai; Risma Rada; Intan Permatasari (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The increasing number of waste is becoming a serious case that must be quickly resolved and resolved. In the coastal area of the Nirwana seaside, BauBau City, there is a lot of plastic waste that has accumulated and is not managed properly, causing zone pollution. Plastic waste has a good and a bad side. One of the positive sides is that plastic waste can be exchanged into creative and innovative products that can improve the economy of coastal coastal communities. Regarding this, we tried to conduct surveys, socialization, and training for people in coastal areas by the sea. Based on the results of the study, this activity generates a fairly large income that matter able in order to make the community prosperous.